Realizing High Photovoltaic Power Densities With Tracking-Integrated Concentrator Photovoltaics - Younes, Kareem; Apostoleris, Harry; Bin Saad, Majed; Al Ghaferi, Amal; Chiesa, Matteo (Frontiers in Energy Research, 2022)
Concentrating photovoltaics (CPV) have long been held up as a solution to low power density in photovoltaics, but due to the requirement of sun tracking have been largely unable to realize high power densities in practically useful settings. The emerging concept of tracking-integrated CPV, in which the sun tracking apparatus is incorporated into the module itself, has the potential to finally achieve this goal by allowing CPV use in building integrated or rooftop settings. In this article, we will provide a status update on TI-CPV and an evaluation of its technical and economic potential with focus on diffuse light collection. We will seek to demonstrate how TI-CPV concepts that are now nearing commercialization are viable to offer, for the first time, the chance for CPV to actually deliver high power densities and high-efficiency utilization of the solar resource in practical settings such that it represents one of the best prospects for CPV to finally gain a foothold in large commercial markets. We identify TI-CPV designs with integrated mechanical tracking and diffuse light transmittance as the closest at resent to commercial feasibility, as the transmitted light offers a potential valuable secondary output. A semi-empirical performance model of such a system yields an annual electrical output of >300 kWh/m2 and 59.4 million lux-hours optical output that are equivalent to 593.4 kWh/m2 if that light would otherwise be provided by LED lamps with 100 lumen/W luminous efficacy. This would indicate that full-system capex of up to $1,600/kW could be viable relative to conventional rooftop PV systems, providing a benchmark for future manufacturing and design improvements.